Interlaminar Discectomy and Selective Foraminotomy in Lumbar Disc Herniation - Manish Garg (Journal of Orthopaedic Surgery, 2001)
Our objective was to assess the clinical outcome of interlaminar discectomy in patients suffering with degenerated lumbar disc lesions. We made a prospective study of 50 consecutive patients who underwent limited lumbar discectomy. The clinicoradiological parameters, type of surgery performed and the post-operative follow up were assessed. We found that interlaminar discectomy without laminotomy was adequate in 33 cases (66%). Most patients requiring laminotomy (17 cases −34%) for discectomy had associated lumbar canal stenosis, herniation at proximal levels (L3–4) and/or sacralization of L5 vertebra. Selective foraminotomy in addition to discectomy was performed in 28 cases (56%). The post-operative results were good in 43 (86%) fair in 6 (12%) and poor subjective in 1 case (2%). No patient was classified as poor objective. In conclusion, interlaminar discectomy without laminotomy is a safe, effective and reliable surgical technique for treating properly selected patients with herniated lumbar disc at L4–5 and L5–S1 levels.